My brilliant friend - Ferrante, Elena (Neapolitan quarter ;, 2020)
The story of Elena and Lila begins in the 1950s in a poor but vibrant neighbourhood on the outskirts of Naples. Growing up on these tough streets the two girls learn to rely on each other ahead of anyone or anything else, as their friendship, beautifully and meticulously rendered, becomes a not-always-perfect shelter from hardship. A memorable portrait of two women, My Brilliant Friend is also the story of a nation. Through the lives of Elena and Lila, Ferrante gives her readers the story of a city and a country undergoing momentous change.